-7(-3b+11)+9(-2-3b)-(-5b-8)=-37

Simple and best practice solution for -7(-3b+11)+9(-2-3b)-(-5b-8)=-37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-3b+11)+9(-2-3b)-(-5b-8)=-37 equation:


Simplifying
-7(-3b + 11) + 9(-2 + -3b) + -1(-5b + -8) = -37

Reorder the terms:
-7(11 + -3b) + 9(-2 + -3b) + -1(-5b + -8) = -37
(11 * -7 + -3b * -7) + 9(-2 + -3b) + -1(-5b + -8) = -37
(-77 + 21b) + 9(-2 + -3b) + -1(-5b + -8) = -37
-77 + 21b + (-2 * 9 + -3b * 9) + -1(-5b + -8) = -37
-77 + 21b + (-18 + -27b) + -1(-5b + -8) = -37

Reorder the terms:
-77 + 21b + -18 + -27b + -1(-8 + -5b) = -37
-77 + 21b + -18 + -27b + (-8 * -1 + -5b * -1) = -37
-77 + 21b + -18 + -27b + (8 + 5b) = -37

Reorder the terms:
-77 + -18 + 8 + 21b + -27b + 5b = -37

Combine like terms: -77 + -18 = -95
-95 + 8 + 21b + -27b + 5b = -37

Combine like terms: -95 + 8 = -87
-87 + 21b + -27b + 5b = -37

Combine like terms: 21b + -27b = -6b
-87 + -6b + 5b = -37

Combine like terms: -6b + 5b = -1b
-87 + -1b = -37

Solving
-87 + -1b = -37

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '87' to each side of the equation.
-87 + 87 + -1b = -37 + 87

Combine like terms: -87 + 87 = 0
0 + -1b = -37 + 87
-1b = -37 + 87

Combine like terms: -37 + 87 = 50
-1b = 50

Divide each side by '-1'.
b = -50

Simplifying
b = -50

See similar equations:

| x-36=44.9 | | x/4-5=7/8 | | 0.217/7 | | 5x+10(x+3)=15 | | 3/6z-6 | | 5x+4y^2= | | 41+2n=2+n | | x^2(x-2)+7x(2-x)-10(2-x)= | | -x(x-3)+x(-2x-8)= | | x^3+15x^2+6x+1=0 | | 9x3/2 | | 9(2+t)-7(t+1)= | | Y=28x-2xsquared | | 5h+6(2h+10)=10 | | 3x-2(5x-y)-(4y+x)= | | w^2(w-3)=350 | | 5x-22=26+x | | Y^2-2y= | | 3.4+z=-7 | | -6th-7=17 | | 1/3x-1/7=8 | | x^2+38x+361=36 | | 5xy-3y+10x-6= | | x-2(x+1)=5+9 | | 15/2x+4=-2 | | 12t=16 | | 2x^2+xy-y^2=2 | | (2c)(3c)=6c | | 16340/40 | | 8*3=7x | | 15/2+4=-2 | | 36-45x+2=42x-49 |

Equations solver categories